On the Sufis’ Intellect-aversion - Mohammad Fanaaii Eshkevari (حکمت اسرا)
In a part of mystical literature, as well as the words of some individuals affiliated with mysticism, intellect and mysticism have been portrayed as being at odds with each other and they were presented as two totally irreconcilable and adverse paths. These people consider intellect not as a source and a way of acquiring knowledge, thus, they give no credit to the achievements of intellect, and consequently, to the Humanities. Based on these people’s viewpoint, intellect is not only an invalid resource of knowledge but also a barrier to acquiring knowledge and a cause of falling into aberration. Interestingly, some of such individuals have resorted to logical reasoning to discredit intellect. In the present paper, some of the argumentations of these people will be addressed and investigated. It is worth emphasizing, however, that the opposition of some mystics, or so-called mystics, to intellect does not indicate as to the opposition of all mystics to intellect or the irreconcilability and conflict of mysticism and intellect, for such oppositions could simply originate from a lack of proper understanding of mysticism and intellect. We believe that not only are not mysticism and intellect irreconcilable, they are mutually confirming and supporting. The pinnacle of this mutual confirmation and support can be seen in Mulla-Sadra’s Transcendent Theosophy.